Interactions of wind energy project siting, wind resource potential, and the evolution of the U.S. power system. (15th May 2021) - Mai, Trieu; Lopez, Anthony; Mowers, Matthew; Lantz, Eric
Abstract: The interactions of wind energy project siting, resource potential, and power system evolution are critical to understand given interest in high renewable energy systems, particularly as wind costs have fallen and grid operators implement solutions to manage variable generation. This study applies an integrative approach that combines spatially-explicit resource potential analysis with high spatial resolution U.S. electricity system modeling. Multiple wind supply curves, representing variations in siting regimes that account for interactions with built infrastructure, regulatory, physical, and social land use factors, are evaluated to determine how siting could influence prospective wind development. Different siting regimes lead to variations in future wind capacity, with the greatest impacts observed under scenarios with high demand for clean energy. With the tightest emissions limit modeled, 2050 onshore wind capacity varied by +7% (49 GW) in the least-restrictive siting regime to a decrease of 37% (270 GW) under the most-constrained case. More-stringent siting restrictions lead to higher electricity prices and emissions that should be weighed with local impacts. Under restrictive siting regimes, wind deployment is also sensitive to transmission availability and wind plant design. Overall, the findings highlight the importance of local land use considerations in regional and national power system planning. Highlights: Prospective wind development is influenced by stringency of siting restrictions. Impact of wind siting is correlated with future demand for clean energy. More-stringent siting restrictions lead to higher electricity costs and emissions. Effects of wind siting depend on transmission availability and wind plant design.